Unraveling taste enhancement mechanism of yeast-inoculated reduced-salt fermented sausage: Proteolysis, taste compound formation, and receptor binding of potential salty/salty taste-enhancing peptides - Dewei Huang; Gaoxin Feng; Iftikhar Hussain Badar; Bayierta Bayinbate; Junhan Fan; Baocai Xu; Linwei Yang; Qianqian Yu; Yingying Hu; Lang Zhang (Food Microbiology, 2026)

Experimental investigation of bubble morphology and instantaneous impact characteristics in submerged jets - Yongfei Yang; Wenxiao Wang; Weidong Shi; Xianglong Wu; Linwei Tan; Yupeng Cao; Yu Lu; Chunhui Ma (Ocean Engineering, 2026)

Salicylic acid-mediated biosynthesis of anti-oomycete diterpenoids in Euphorbia lathyris L. suspension cells - Pirui Li; Xi Sun; Guodong Zhang; Bi Wang; Chenxing Xiao; Mei Tian; Shu Xu; Hui Liu; Xu Feng; Linwei Li; Wanli Zhao; Yu Chen (Plant Cell Reports, 2026)

Effect of ultrasonication on the structure and stability of protein modified liposomes - Linwei Zhao; Libin Sun; Weining Wang; Mingzhe Pan; Lanxia Qin; Dianyu Yu (Food Hydrocolloids, 2026)

Preparation of high-specificity monoclonal antibody based on rational hapten design and development of immunoassay for accurate detection of dexamethasone in milk and animal tissues - Hongfei Yang; Liangni Qin; Jiaxu Xiao; Xiaoming Pan; Shiyun Han; Linwei Zhang; Jixiang Liang; Yu Si; Hao Wen; Long Li; Xingyu Wang; Xiaojuan Zhang; et al. (Food Bioscience, 2025)

Localized surface plasmon enhancement strategy with synergistic dual-mechanism fluorescence quenching for developing highly sensitive lateral flow immunoassays - Mingyue Ding; Hao Wen; Long Li; Yu Si; Jixiang Liang; Shixiang Wu; Linwei Zhang; Hongfei Yang; Shiyun Han; Xiaoming Pan; Yiting Wang; Jiacan Wang; et al. (Chemical Engineering Journal, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

Synergistic treatment of respiratory syncytial virus induced pneumonia by multifunctional Baicalin-Resveratrol self-assembled nanomedicine - Chenqi Chang; Yu Zheng; Chang Lu; Ying Ma; Liang Wu; Yunyu Zhang; Lili Lin; Liang Guo; XiuZhen Chen; Linwei Chen; Jianming Cheng; Rui Chen (Chemical Engineering Journal, 2025)

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)

Influence of interannual anomalies in late autumn Arctic sea ice concentration on Asian winter cold extremes - Cen Wang; Hui Su; Jianqiu Zheng; Linwei Jiang; Shiwei Yu; Yanjia Wang (Climate Dynamics, 2025)
In early 2008, densely populated areas of Asia suffered significant societal losses due to widespread cold extremes. Previous studies have suggested that variations in Arctic sea ice might influence the occurrence of Asian Winter Cold Extremes (AWCE). However, there is still debate over the precise nature and geographical specificity of these teleconnections. This study analyzes the frequency of AWCE from 1979 to 2024, and shows that it is significantly negatively correlated with anomalies in late autumn sea ice concentration (SIC) in the southern (SICS) Arctic on the interannual time scale. The potential physical mechanisms behind these correlations can be explained as follows: on a mean winter scale, anomalous decreases in SICS strengthens the ridge and deepens the trough over the Eurasian continent in the mid-troposphere, due to the excitation of Rossby waves. This, in turn, enhances anomalous northerly winds on the Siberian High’s eastern flank, particularly affecting Asia, thereby fostering conditions conducive to AWCE. On the synoptic scale, negative SICS anomalies promote more blocking highs over the northern Eurasian continent, thereby increasing the occurrence of AWCE.

Combined multispectral analysis and molecular docking to research the interaction of soybean isolate protein with different kinds of phospholipid liposomes and its effect on liposome properties - Linwei Zhao; Chunlei Liu; Tong Wang; Libin Sun; Fei Wu; Dianyu Yu (Food Chemistry, 2025)

Establishment of virus-induced gene silencing in Euphorbia lathyris L. and its application in casbene synthase (CBS) gene functional analysis - Wei Lyu; Mei Tian; Long Huang; Bi Wang; Pirui Li; Wanli Zhao; Linwei Li; Xu Feng; Shu Xu; Yu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A reversible solar photothermal Li-CO2 battery enabled by engineering 3D plasmonic Cr-N-Ru catalysts assembled on carbon-free Si NP cathode - Shimin Chen; Junnan Han; Zhihuan Li; Zijie Lin; Min Wang; Hucheng Song; Xiaodong Pi; Dongke Li; Linwei Yu; Jun Xu; Kunji Chen (Chemical Engineering Journal, 2025)

Genetic advancements and future directions in ruminant livestock breeding: from reference genomes to multiomics innovations - Songsong Xu; Zhanerke Akhatayeva; Jiaxin Liu; Xueyan Feng; Yi Yu; Bouabid Badaoui; Ali Esmailizadeh; Juha Kantanen; Marcel Amills; Johannes A. Lenstra; Anna M. Johansson; David W. Coltman; et al. (Science China Life Sciences, 2025)

Electroformation and characterization of soybean protein isolate hydrolysates-modified liposomes - Libin Sun; Linwei Zhao; Zhe Huang; Fei Wu; Mingzhe Pan; Dianyu Yu (Food Hydrocolloids, 2025)

In vitro simulated digestive properties of Monascus vinegar melanoidins, and cytoprotective functions on Caco-2 cells - Kuaitian Wang; Yuwei Li; Xiaojia Bian; Chen Wang; Donghui Geng; Linwei Yu; Yongqiang Cheng; Hongbin Chen; Ning Tang (Food Research International, 2025)

Records of Fukushima accident-derived cesium-137 in the Chukchi Sea sediment: Implication for a new time marker? - Xu Ren; Jinlong Wang; Gi Hoon Hong; Linwei Li; Qiangqiang Zhong; Dekun Huang; Tao Yu; Jinzhou Du (Science China Earth Sciences, 2024)

Effects of Carbon Fiber Reinforced Epoxy Composite Waste On Seed Germination and Seedling Growth of Plants - Anping Zhu; Shengzong Ci; Longjiang Yu; Huawei Jiang; Linwei Song; Chengrui Di; Kun Qiao (Journal of Crop Health, 2024)

Baseline sensitivity and resistance risk of Sclerotinia sclerotiorum to glabridin and the possible anti-fungal mechanism - Shu Xu; Chenyang Liu; Jin Chen; Linwei Li; Siwei Qiao; Mei Tian; Qian Zhou; Xingzeng Zhao; Yu Chen; Fei Liu; Xu Feng (Pesticide Biochemistry and Physiology, 2024)

Design of 3D printing superhydrophilic pyramid-shaped porous materials for oil-in-water emulsion separation and visualization of separation mechanism - Liangliang Shen; Yu yang; Hongyin Li; Shilun Shi; Linwei Shi; Zhiying Ren (Chemical Engineering Journal, 2024)

Discovery of ElABCG39: a key player in ingenol transmembrane efflux identified through genome-wide analysis of ABC transporters in Euphorbia lathyris L. - Guyin Lin; Pirui Li; Linwei Li; Ruyuan Wang; Wanli Zhao; Mei Tian; Junzhi Wu; Shu Xu; Yu Chen; Xu Feng (Plant Cell Reports, 2024)

Preparation of high-affinity and high-specificity monoclonal antibody and development of ultra-sensitive immunoassay for the detection of 1-aminohydantoin, the metabolite of nitrofurantoin - Hongfei Yang; Liangni Qin; Hao Wen; Mingyue Ding; Linwei Zhang; Jiaxu Xiao; Jixiang Liang; Yiting Liu; Ziyan Yu; Dapeng Peng (Food Chemistry, 2024)

Complex phospholipid liposomes co-encapsulated of proanthocyanidins and α-tocopherol: Stability, antioxidant activity and in vitro digestion simulation - Linwei Zhao; Donghua Wang; Jiaye Yu; Xu Wang; Tong Wang; Dianyu Yu; Walid Elfalleh (Food Bioscience, 2024)

Targeted discovery of unusual diterpenoids with anti-fungal activity from the root of Euphorbia lathyris - Yiwei Wang; Shu Xu; Guodong Zhang; Pirui Li; Chenyang Liu; Jiarui Zhou; Xu Feng; Linwei Li; Yu Chen (Phytochemistry, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Research on the Penetration Coefficient During the Rock Drilling Process by Cyclic Impact - Jinguang Li; Yu Liu; Linwei Wang; Yumeng Sun; Xin Li; Junjie Wang (Rock Mechanics and Rock Engineering, 2024)

Automatic identification of illegal construction and demolition waste landfills: A computer vision approach - Qiaoqiao Yong; Huanyu Wu; Jiayuan Wang; Run Chen; Bo Yu; Jian Zuo; Linwei Du (Waste Management, 2023)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Spatial pattern assessment of dengue fever risk in subtropical urban environments: The case of Hong Kong - Shi Yin; Junyi Hua; Chao Ren; Runxi Wang; André Ibáñez Weemaels; Benoit Guénard; Yuan Shi; Tsz-Cheung Lee; Hsiang-Yu Yuan; Ka Chun Chong; Linwei Tian (Landscape and Urban Planning, 2023)

Thallium release from biochar-amended soil to runoff in laboratory experiments - Lezhang Wei; Dafeng Cai; Fangqing Li; Yu Liu; Linwei Zeng; Dinggui Luo; Xuexia Huang; Tangfu Xiao; Hang Shi; Haiqi Yan (Environmental Pollution, 2023)

Contrasting behaviors of 210Po, 210Pb and 234Th in the East China Sea during a severe red tide: Enhanced scavenging and promoted fractionation - Qiangqiang Zhong; Linwei Li; Viena Puigcorbé; Dekun Huang; Tao Yu; Jinzhou Du (Acta Oceanologica Sinica, 2022)

A comparison of next-generation sequencing with clone sequencing in the diet analysis of Asian great bustard - Minghao Gong; Yu Ning; Morigen Han; Chenyang Zhao; Jingxing Tian; Linwei Li; Hongye Xiao; Gang Liu (Conservation Genetics Resources, 2019)

Who is more vulnerable to death from extremely cold temperatures? A case-only approach in Hong Kong with a temperate climate - Hong Qiu; Linwei Tian; Kin-fai Ho; Ignatius T. S. Yu; Thuan-Quoc Thach; Chit-Ming Wong (International Journal of Biometeorology, 2016)

Responses of the functional structure of soil microbial community to livestock grazing in the T ibetan alpine grassland - Yunfeng Yang; Linwei Wu; Qiaoyan Lin; Mengting Yuan; Depeng Xu; Hao Yu; Yigang Hu; Jichuang Duan; Xiangzhen Li; Zhili He; Kai Xue; Joy van Nostrand; et al. (Global Change Biology, 2013)
Microbes play key roles in various biogeochemical processes, including carbon (C) and nitrogen (N) cycling. However, changes of microbial community at the functional gene level by livestock grazing, which is a global land‐use activity, remain unclear. Here we use a functional gene array, GeoChip 4.0, to examine the effects of free livestock grazing on the microbial community at an experimental site of T ibet, a region known to be very sensitive to anthropogenic perturbation and global warming. Our results showed that grazing changed microbial community functional structure, in addition to aboveground vegetation and soil geochemical properties. Further statistical tests showed that microbial community functional structures were closely correlated with environmental variables, and variations in microbial community functional structures were mainly controlled by aboveground vegetation, soil C/N ratio, and NH 4 + ‐N . In‐depth examination of N cycling genes showed that abundances of N mineralization and nitrification genes were increased at grazed sites, but denitrification and N‐reduction genes were decreased, suggesting that functional potentials of relevant bioprocesses were changed. Meanwhile, abundances of genes involved in methane cycling, C fixation, and degradation were decreased, which might be caused by vegetation removal and hence decrease in litter accumulation at grazed sites. In contrast, abundances of virulence, stress, and antibiotics resistance genes were increased because of the presence of livestock. In conclusion, these results indicated that soil microbial community functional structure was very sensitive to the impact of livestock grazing and revealed microbial functional potentials in regulating soil N and C cycling, supporting the necessity to include microbial components in evaluating the consequence of land‐use and/or climate changes.

Increasing trend of primary NO2 exhaust emission fraction in Hong Kong - Linwei Tian; Sarah R. Hossain; Hualiang Lin; Kin Fai Ho; Shun Cheng Lee; Ignatius T. S. Yu (Environmental Geochemistry and Health, 2011)